2015
DOI: 10.1038/srep09297
|View full text |Cite
|
Sign up to set email alerts
|

Probing Immobilization Mechanism of alpha-chymotrypsin onto Carbon Nanotube in Organic Media by Molecular Dynamics Simulation

Abstract: The enzyme immobilization has been adopted to enhance the activity and stability of enzymes in non-aqueous enzymatic catalysis. However, the activation and stabilization mechanism has been poorly understood on experiments. Thus, we used molecular dynamics simulation to study the adsorption of a-chymotrypsin (a-ChT) on carbon nanotube (CNT) in aqueous solution and heptane media. The results indicate that a-ChT has stronger affinity with CNT in aqueous solution than in heptane media, as confirmed by more adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 58 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…The binding free energy is estimated as the difference The entropic changes are ignored as in previous recent studies. 56 , 95 , 96 , 125 The binding free energy of the dimer complex is thus obtained as where Δ E electrostatic , Δ E vdW , and Δ E internal are the changes in the electrostatic, vdW, and bonded energies, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The binding free energy is estimated as the difference The entropic changes are ignored as in previous recent studies. 56 , 95 , 96 , 125 The binding free energy of the dimer complex is thus obtained as where Δ E electrostatic , Δ E vdW , and Δ E internal are the changes in the electrostatic, vdW, and bonded energies, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…2 , the adsorption processes of the two models both present several jumps for the number of absorbed atoms and the contact areas. Previous theoretical studies on some typical proteins immobilized to graphene 28 and CNT 27 , 29 also showed the multistep adsorption. Different from short jump times revealed by the previous works, the multistep adsorption in the work covers a relatively long timescale, reaching several hundred nanoseconds.…”
Section: Resultsmentioning
confidence: 86%
“…5 C. A hydrogen bond is considered to be formed if the donor-acceptor distance is <3.5 Å and the hydrogen-donor-acceptor angle is <30 . If a hydrogen bond survives >90% of the trajectory time, we consider it to be a stable bond (34). seventh trajectory.…”
Section: Resultsmentioning
confidence: 99%